Rubber composition, crosslinkable rubber composition, method for producing molded product of rubber composition, and tire tread
Patent Information
- Application Number
- JP2020154300
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-09-15
AI Technical Summary
【0010】 本発明によれば、実用上十分な成形性を有し、ゴム組成物中の組成ムラが発生し難く、タイヤの材料として用いたときに優れた引張強度及び耐摩耗性を示す、ゴム組成物が得られる。
Smart Images

Figure 0007652546000001 
Figure 0007652546000002 
Figure 0007652546000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition, a rubber composition for crosslinking, a method for producing a molded article of the rubber composition, and a tread for a tire. [Background technology]
[0002] In recent years, in the field of rubber materials for tire treads, sheets, films, and asphalt modification, rubber compositions containing rubber-like polymers having an ethylene structure and into which crosslinkable unsaturated groups have been introduced have been proposed for the purpose of increasing mechanical strength and compression set (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 150645 [Patent Document 2] International Publication No. 2019 / 151126 [Patent Document 3] International Publication No. 2019 / 151127 [Patent Document 4] International Publication No. 2019 / 078083 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the rubbery polymers which have been proposed so far and have an ethylene structure and contain a crosslinkable unsaturated group tend to have a high viscosity. Due to the high viscosity of such rubbery polymers, when a sheet containing the rubbery polymer is produced in the tire production process, there is a problem that the surface of the rubber composition sheet before vulcanization becomes rough and the sheet is easily torn. Furthermore, when a rubber-like polymer having an ethylene structure is produced by solution polymerization, the high viscosity of the rubber-like polymer becomes a problem. Specifically, the crumbs of the rubber-like polymer obtained in the steam stripping step apply more torque than necessary to the drying extruder, which causes an overload on the drying extruder.
[0005] The problems with the rubbery polymer having an ethylene structure as described above can be improved by reducing the molecular weight of the rubbery polymer. However, reducing the molecular weight of the rubbery polymer has the problem that the mechanical properties, particularly the tensile strength and abrasion resistance, of the resulting tire composition tend to deteriorate.
[0006] As a method for improving the processability during the production of a tire composition while maintaining the mechanical properties of the tire composition, there is a method in which a rubber-like polymer of a specific molecular weight is mixed with a rubber-like polymer of a high molecular weight to obtain a rubber composition. However, since rubbery polymers having an ethylene structure have high solution viscosity, a high molecular weight rubbery polymer solution and a low molecular weight rubbery polymer solution are difficult to mix, resulting in a non-uniform solution. As a result, there is a problem in that the ratio of high molecular weight components to low molecular weight components in the rubber composition obtained from the mixed solution is unlikely to be the target ratio.
[0007] Therefore, an object of the present invention is to provide a rubber composition which has sufficient moldability for practical use, is less likely to cause compositional unevenness in the rubber composition, and exhibits excellent tensile strength and abrasion resistance when used as a tire material. [Means for solving the problem]
[0008] The present inventors have conducted intensive research and investigation in order to solve the problems of the conventional technology described above, and as a result have found that by containing a rubber-like polymer having a specific structure and a specific molecular weight in a specific ratio, the moldability of the rubber composition is less likely to be reduced, compositional unevenness is less likely to occur in a rubber composition molded product even after molding, and the rubber composition exhibits excellent tensile strength and abrasion resistance when used in a tire, thereby completing the present invention. That is, the present invention is as follows.
[0009] [1] The iodine value is 10 to 270 g / 100 g. Contains 3% by mass or more of an ethylene structure, The amount of vinyl aromatic monomer blocks is 10% by mass or less, The content of vinyl aromatic monomer units is 5% by mass or more, In the molecular weight distribution of the rubber-like polymer determined by gel permeation chromatography (GPC), there is at least one peak at a molecular weight of 350,000 or more; and has at least one peak in the molecular weight range of 5,000 to less than 350,000; In a gel permeation chromatography (GPC) measurement with a viscometer, the average branching degree of a rubber-like polymer having a molecular weight of 350,000 or more is 3 or more. A rubber composition in which, in a GPC molecular weight distribution curve, the area of a rubber-like polymer having a molecular weight of 350,000 or more is AA, and the area of a rubber-like polymer having a molecular weight of 5,000 to less than 350,000 is BA, the ratio of BA to the total area of AA and BA (BA) / (AA+BA) is 50% or more and 90% or less. [2] The rubber composition according to [1] above, wherein the highest peak top molecular weight Mp in a GPC molecular weight distribution curve is 650,000 or more. [3] The content of α-olefins other than vinyl aromatic monomer units is 15% by mass or more; The rubber composition according to [1] or [2] above. [4] The rubber composition according to any one of [1] to [3] above, which contains a nitrogen atom. [5] The rubber composition according to any one of [1] to [4] above, wherein the modification rate measured by a column adsorption GPC method is 20 mass % or more. [6] The modification rate measured by column adsorption GPC method is The modification rate of the rubber-like polymer having a molecular weight of 350,000 or more is 60 mass% or more. The rubber composition according to any one of [1] to [5] above. [7] The rubber composition according to any one of [1] to [6] above, having a silicon content of 50 ppm or more. [8] The rubber composition according to any one of [1] to [7] above, wherein the branching degree of the rubber polymer in the molecular weight range of 350,000 or more is greater than the branching degree of the rubber polymer in the molecular weight range of less than 350,000. [9] The rubber composition according to any one of [1] to [8] above, having a Mooney relaxation ratio (MSR) of 0.5 or less.
[10] The rubber composition according to any one of [1] to [9] above, A cross-linking agent; Contains The crosslinking agent is contained in an amount of 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the rubber component. Crosslinkable rubber composition.
[11] A method for producing a rubber composition molded article using the rubber composition according to any one of [1] to [9] above or the rubber composition for crosslinking according to
[10] above, A step of polymerizing a rubber-like polymer A having a peak top of a molecular weight of 350,000 or more; A step of polymerizing a rubber-like polymer B having a peak top at a molecular weight of 5,000 to less than 350,000; A step of mixing the rubbery polymer A and the rubbery polymer B in a solution to obtain a mixed solution; removing the solvent from the mixed solution to obtain a rubber composition; A step of molding using the rubber composition; having, A method for producing a rubber composition molded article.
[12] A method for producing a rubber composition molded article using the rubber composition according to any one of [1] to [9] above or the rubber composition for crosslinking according to
[10] above, A step of polymerizing a rubber-like polymer A having a peak top of a molecular weight of 350,000 or more; A step of polymerizing a rubber-like polymer B having a peak top at a molecular weight of 5,000 to less than 350,000; adding two or more types of functionalizing agents having different branching degrees to the rubber polymer A and the rubber polymer B, respectively, to functionalize the polymer chain ends; removing the solvent from the polymerization solution to obtain a rubber composition; The method includes a step of molding the obtained rubber composition. A method for producing a rubber composition molded article.
[13] A tire tread comprising the rubber composition according to any one of [1] to [9] above or the rubber composition for crosslinking according to
[10] above. Effect of the Invention
[0010] According to the present invention, a rubber composition can be obtained which has sufficient moldability for practical use, is less susceptible to compositional irregularities in the rubber composition, and exhibits excellent tensile strength and abrasion resistance when used as a tire material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment. The present invention can be practiced with appropriate modifications within the scope of the gist of the present invention.
[0012] [Rubber Polymer] The rubber composition of the present embodiment is The iodine value is 10 to 270 g / 100 g. Contains 3% by mass or more of an ethylene structure, The amount of vinyl aromatic monomer blocks is 10% by mass or less, The content of vinyl aromatic monomer units is 5% by mass or more, In the molecular weight distribution of the rubber-like polymer determined by gel permeation chromatography (GPC), there is at least one peak at a molecular weight of 350,000 or more; and has at least one peak in the molecular weight range of 5,000 to less than 350,000; In a gel permeation chromatography (GPC) measurement with a viscometer, the average branching degree of a rubber-like polymer having a molecular weight of 350,000 or more is 3 or more. In the GPC molecular weight distribution curve, When the area of the rubber-like polymer having a molecular weight of 350,000 or more is AA and the area of the rubber-like polymer having a molecular weight of 5,000 to less than 350,000 is BA, the ratio of BA to the total area of AA and BA (BA) / (AA+BA) is 50% or more and 90% or less.
[0013] <Iodine value> The rubber composition of the present embodiment has an iodine value of 10 to 270 g / 100 g. From the viewpoint of ease of crosslinking, the iodine value is 10 g / 100 g or more, preferably 15 g / 100 g or more, more preferably 30 g / 100 g or more, even more preferably 50 g / 100 g or more, and even more preferably 70 g / 100 g or more. On the other hand, from the viewpoint of weather resistance of the rubber composition molded article of the present embodiment, it is 270g / 100g or less, preferably 200g / 100g or less, more preferably 150g / 100g or less, even more preferably 110g / 100g or less, and even more preferably 80g / 100g or less. The iodine value can be measured according to the method described in "JIS K 0070:1992". The iodine value is the amount of halogen that reacts with 100 g of the target substance converted into grams of iodine, so the unit of the iodine value is "g / 100 g". When a conjugated diene monomer is used as a monomer for polymerization, double bonds remain even after polymerization. Therefore, in the method for producing a rubber composition described below, for example, when a conjugated diene monomer is copolymerized with a vinyl aromatic monomer, the iodine value of the rubber composition decreases as the content of the conjugated diene monomer decreases, and when the conjugated diene monomer is hydrogenated, the iodine value decreases as the hydrogenation rate increases. The iodine value of the rubber composition can be controlled within the above numerical range by adjusting the amount of the conjugated diene monomer having an unsaturated bond added, the polymerization conditions such as the polymerization time and the polymerization temperature, and the amount of hydrogen added in the hydrogenation step, the hydrogenation time, and other conditions.
[0014] <Ethylene structure content> The rubber composition of the present embodiment contains 3% by mass or more of an ethylene structure. When the ethylene structure content is 3% by mass or more, the mechanical strength is excellent. The ethylene structure content is preferably 5% by mass or more, more preferably 30% by mass or more, and further preferably 40% by mass or more. The ethylene structure content is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. When the ethylene structure is 90% by mass or less, the rubber composition of the present embodiment has excellent moldability. The ethylene structure of the rubber composition includes various forms, such as an ethylene structure obtained by copolymerizing an ethylene monomer, and an ethylene structure obtained by polymerizing a conjugated diene monomer and then hydrogenating the polymer. For example, when a 1,4-butadiene unit is hydrogenated, two ethylene structures are obtained, and when a 1,4-isoprene unit is hydrogenated, one propylene structure and one ethylene structure are obtained. The ethylene structure of the rubber composition and the rubber-like polymer constituting the rubber composition can be measured by the method described in the Examples below, and can be controlled within the above numerical range by the amount of ethylene added, the amount of conjugated diene monomer added, the hydrogenation rate, etc.
[0015] <Vinyl aromatic monomer block content> The rubber composition of the present embodiment has a vinyl aromatic monomer block content of 10% by mass or less. The vinyl aromatic monomer block refers to a block in which eight or more vinyl aromatic monomer units are linked together. When the vinyl aromatic monomer block content is 10% by mass or less, the sheet-like or block-like molded product using the rubber composition of the present embodiment has excellent cuttability during measurement. Specifically, there is an advantage that the sheet or block-like bale containing the rubber composition can be cut without being too hard in the process of cutting the sheet or block-like bale with a large cutter. The vinyl aromatic monomer block content is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. From the viewpoint of flexibility of the rubber composition or tire composition, it is preferable that the vinyl aromatic monomer block has a small number of blocks in which 30 or more vinyl aromatic monomer units are chained, or that there is no block. Specifically, when the polymer is a butadiene-styrene copolymer, the morphology of the vinyl aromatic monomer block can be determined by decomposing the polymer by the Kolthoff method (the method described in I.M.Kolthoff, et al., J.Polym.Sci.1,429(1946)) and analyzing the amount of polystyrene insoluble in methanol. As another method, the morphology can be determined by a known method such as measuring the chain of styrene units using NMR, as described in International Publication No. 2014-133097. The vinyl aromatic monomer block content of the rubber composition can be controlled within the above numerical range by the method of adding the vinyl aromatic monomer, the addition of the polar substance, the polymerization temperature, etc. More specifically, the block content can be reduced by not supplying the vinyl aromatic monomer alone to the reactor but supplying it together with the conjugated diene monomer, and there is a tendency that the vinyl aromatic monomer block content can be further reduced by increasing the amount of polar substance added or raising the polymerization temperature.
[0016] <Vinyl aromatic monomer unit content> In the rubber composition of the present embodiment, the content of vinyl aromatic monomer units is 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and even more preferably 20% by mass or more, from the viewpoints of deformation resistance during transportation of a molded body, and breaking strength and wet skid resistance when used in a tire tread. On the other hand, from the viewpoints of cuttability during measurement of the sheet-like or block-like molded body, preventing aggregation of the rubber component in the solvent removal step, ease of adjusting the metal amount in the rubber composition, and fuel economy and abrasion resistance when used in a tire tread, the content of vinyl aromatic monomer units is preferably 45 mass% or less, more preferably 40 mass% or less, and even more preferably 35 mass% or less. In addition, in the manufacturing process of the rubber composition of this embodiment, when multiple rubbery polymer solutions are mixed together to obtain a rubber composition solution, from the viewpoint of reducing the solution viscosity, the content of vinyl aromatic monomer units is preferably 5 mass% or more, more preferably 8 mass% or more, and even more preferably 10 mass% or more. The content of the vinyl aromatic monomer unit in the rubber composition of the present embodiment can be measured by the method described in the Examples described later, and can be controlled to be within the above numerical range by adjusting the amount of the vinyl aromatic monomer added in the polymerization step.
[0017] <Molecular weight of rubber composition> The rubber composition of the present embodiment has at least one peak at a molecular weight of 350,000 or more in the molecular weight distribution determined by gel permeation chromatography (GPC). As a result, a tire molded article using the rubber composition of this embodiment can have high abrasion resistance. More preferably, it has at least one peak at 400,000 or more, and even more preferably it has at least one peak at 450,000 or more. On the other hand, from the viewpoint of sheet moldability of the rubber composition, the lowest molecular weight peak in the rubber composition is preferably 220,000 or less, more preferably 200,000 or less, and even more preferably 180,000 or less. In addition, the rubber composition of the present embodiment has at least one peak in the molecular weight range of 5,000 to less than 350,000. From the viewpoint of suppressing stickiness of a molded article using the rubber composition and obtaining high mechanical strength, the peak molecular weight of the rubber composition of the present embodiment in this molecular weight range is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 30,000 or more. On the other hand, by having a peak molecular weight of less than 350,000, good moldability can be obtained when processing a tire molded article using the rubber composition. It is more preferably 330,000 or less, and even more preferably 300,000 or less. The molecular weight of the rubber composition can be calculated from the polystyrene-equivalent molecular weight measured by GPC (gel permeation chromatography), and can be measured by the method described in the examples below. In addition, the peak molecular weight in the rubber composition of this embodiment can be controlled as described above by producing rubbery polymers of multiple molecular weights, adding multiple types of branching agents, or mixing previously prepared rubbery polymers of multiple molecular weights in the production process of the rubber composition. The weight average molecular weight of the entire rubber composition is preferably 500,000 or more, more preferably 550,000 or more, and even more preferably 600,000 or more, from the viewpoint of abrasion resistance.
[0018] <Degree of branching of rubber polymer constituting rubber composition> The rubber composition of this embodiment has at least one peak at 350,000 or more in the molecular weight distribution of the rubbery polymer determined by GPC, and the rubbery polymer having a molecular weight of 350,000 or more has an average branching degree of 3 or more. Since the rubber-like polymer having a molecular weight of 350,000 or more has an average branching degree of 3 or more, good sheet moldability can be obtained when the rubber composition of the present embodiment is processed, and good mixability can be obtained when rubber-like polymers are mixed to obtain a rubber composition solution. The average branching degree of the rubbery polymer having a molecular weight of 350,000 or more is preferably 4 or more branches, more preferably 6 or more branches, even more preferably 10 or more branches, and even more preferably 12 or more branches. On the other hand, from the viewpoint of abrasion resistance when made into a tire, the average branching degree of the rubber-like polymer having a molecular weight of 350,000 or more is preferably 84 branches or less, more preferably 60 branches or less, even more preferably 40 branches or less, and even more preferably 30 branches or less.
[0019] The degree of branching of the rubber-like polymer constituting this embodiment can be determined from the value of the shrinkage factor (g') measured by a GPC-light scattering method with a viscosity detector. In general, a polymer having branches tends to have a smaller molecular size when compared to a linear polymer having the same absolute molecular weight. The shrinkage factor (g') is a measure of the ratio of the molecular size to that of a linear polymer of the same assumed absolute molecular weight. In other words, the greater the degree of branching of a polymer, the smaller the shrinkage factor (g') tends to be. In this specification, the intrinsic viscosity is used as an index of molecular size, and for linear polymers, the intrinsic viscosity [η] = -3.927 × M 0.743 It is used as following the relation: The shrinkage factor for each molecular weight of the rubber-like polymer constituting the rubber composition is calculated, and the average degree of branching for each molecular weight region can be calculated from the average value of the shrinkage factors for each molecular weight region (average shrinkage factor value). The average shrinkage factor tends to decrease as the branching degree increases, and when the branching degree is 1, the average shrinkage factor is 0.60 to 0.85, when the branching degree is 3 or more, the average shrinkage factor is less than 0.60, and when the branching degree is 6 or more, the average shrinkage factor is 0.55 or less. The average shrinkage factor value can be measured by the method described in the Examples below, and the branching degree of the rubber polymer can be determined thereby. Here, "branch" refers to a structure formed by direct or indirect bonding of one polymer to another polymer. Also, "degree of branching" refers to the number of polymers that are directly or indirectly bonded to one branch. For example, when five rubber-like polymer chains (described below) are indirectly bonded to each other via a coupling agent residue (described below), the degree of branching is 5. The degree of branching of the rubber polymer constituting the rubber composition of the present embodiment can be controlled by the combination of the type and amount of the branching agent, which will be described later, and the type and amount of the coupling agent.
[0020] <Degree of branching of rubber-like polymers with molecular weight of less than 350,000> The branching degree of the rubbery polymer having a molecular weight of less than 350,000 constituting the rubber composition of this embodiment is preferably smaller than the branching degree of the rubbery polymer having a molecular weight of 350,000 or more, specifically, preferably 2 or less branches, more preferably 1. When the branching degree of the rubbery polymer having a molecular weight of less than 350,000 is 2 or less branches, good mixability can be obtained when mixing rubbery polymer solutions together.
[0021] <Molecular weight distribution of rubber-like polymer> The molecular weight distribution (=weight average molecular weight / number average molecular weight) of the rubber-like polymer constituting the rubber composition of the present embodiment is preferably 2.5 or less, more preferably 2.0 or less, and even more preferably 1.8 or less, from the viewpoint of fuel saving properties when the rubber composition of the present embodiment is used in a tire. On the other hand, from the viewpoint of processability when the rubber composition of the present embodiment is made into a rubber composition for crosslinking, the molar ratio is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.4 or more.
[0022] <Area ratio of a given molecular weight range in a molecular weight distribution curve> In the molecular weight distribution curve of the rubber composition of this embodiment obtained by a GPC method, when the peak area of a molecular weight of 350,000 or more is AA and the peak area of a molecular weight of 5,000 to less than 350,000 is BA, the ratio of BA to the total area of AA and BA (BA / (AA+BA)) is 50% or more and 90% or less. By setting the ratio of BA to the total area of AA and BA at 50% or more, good sheet moldability can be obtained when processing the rubber composition. From the same viewpoint, the ratio of BA is preferably 60% or more, and more preferably 70% or more. On the other hand, by making the ratio of BA to the total area of AA and BA 90% or less, the rubber composition has high mechanical strength and abrasion resistance when made into a tire. From the viewpoint of mechanical strength, it is preferably 85% or less, and more preferably 80% or less. The presence of a rubber-like polymer having a molecular weight of 350,000 or more in a rubber composition adversely affects the sheet processing of the rubber composition, while the presence of a rubber-like polymer having a molecular weight of less than 350,000 contributes to good processability. Therefore, by adjusting the proportion of the polymers having a molecular weight of about 350,000, sufficient processability as a rubber composition can be obtained. The molecular weight distribution of the rubber composition can be calculated from the number average molecular weight and weight average molecular weight in terms of polystyrene measured by GPC, and can be measured by the method described in the examples below. The AA and BA of the rubber composition can be calculated by the GPC method described later in the Examples. The ratio (BA / (AA+BA)) can be controlled within the above numerical range by adjusting the molecular weight and ratio of the constituent rubbery polymers in the production process of the rubber composition of this embodiment.
[0023] In the rubber composition of the present embodiment, the highest peak top molecular weight Mp in the GPC molecular weight distribution curve is preferably 650,000 or more. When the Mp is 650,000 or more, excellent wear resistance can be obtained. The peak top molecular weight Mp is more preferably 680,000 or more, and further preferably 700,000 or more. The peak top molecular weight Mp can be controlled within the above numerical range by reducing the amount of polymerization initiator added or increasing the branching degree of the coupling agent.
[0024] <Monomer units that allow rubber polymers to contain unsaturated groups> The rubber-like polymer constituting the rubber composition of the present embodiment preferably contains 2 mass % or more of a monomer unit having an unsaturated group in addition to the conjugated diene monomer unit, myrcene, and the like. From the viewpoints of economy and manufacturability, the rubber-like polymer constituting the rubber composition of the present embodiment more preferably contains conjugated diene monomer units. Since the conjugated diene monomer units and myrcene have double bonds, the resulting rubber-like polymer has crosslinkable unsaturated groups. The content of conjugated diene monomer units and monomer units having an unsaturated group such as myrcene in the rubber composition is closely related to the above-mentioned iodine value. By having the content of the conjugated diene monomer unit or the monomer unit having an unsaturated group such as myrcene at 2% by mass or more, the composition is excellent in terms of ease of crosslinking. The content of the conjugated diene monomer unit is more preferably 3% by mass or more, and further preferably 6% by mass or more. The content of the conjugated diene monomer unit or the monomer unit having an unsaturated group such as myrcene is preferably 50% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less, which provides excellent weather resistance and resistance to deterioration over time. Of the conjugated diene monomer units and monomer units having an unsaturated group such as myrcene, the conjugated diene monomer units are preferred from the viewpoints of economy and productivity. The content of the conjugated diene monomer unit or the monomer unit having an unsaturated group such as myrcene in the rubber-like polymer can be measured by the method described in the Examples described later, and can be controlled within the above-mentioned numerical range by the amount of the conjugated diene monomer unit or the monomer having an unsaturated group such as myrcene added or the hydrogenation rate of the conjugated diene monomer, which will be described later. The hydrogenation rate of the rubber composition, and the inter- or intra-molecular distribution of monomers such as ethylene, conjugated diene monomer, myrcene, and vinyl aromatic monomer are not particularly limited, and may be uniform, non-uniform, or distributed.
[0025] <α-olefin content in rubber composition> In the rubber composition of this embodiment, the α-olefin content in all monomer units excluding vinyl aromatic monomer units is preferably 15 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, from the viewpoint of productivity of the rubber-like polymer. On the other hand, from the viewpoint of mechanical strength when used in a tire, it is preferably 70 mass % or less, more preferably 60 mass % or less, even more preferably 55 mass % or less, and even more preferably 50 mass % or less. When the rubber-like polymer constituting the rubber composition of the present embodiment is produced by hydrogenating a polymer or copolymer of a conjugated diene monomer, the α-olefin content can be controlled by adjusting the conjugated diene monomer content, the vinyl bond content, or the hydrogenation rate before the hydrogenation reaction. Specifically, when 1,2-vinylbutadiene is hydrogenated, it becomes butylene, which is an α-olefin structure. The α-olefin content of the rubbery polymer can be measured by the method described in the Examples.
[0026] <Modification of the rubber polymer constituting the rubber composition> From the viewpoint of fuel economy when made into a tire, the rubber composition of the present embodiment preferably contains a rubber-like polymer constituting the rubber composition, and more preferably contains a nitrogen atom.
[0027] The rubber composition of the present embodiment preferably has a modification rate of 20% by mass or more as measured by a column adsorption GPC method. With a modification rate of 20% by mass or more, excellent fuel saving performance can be obtained. The modification rate of the rubber composition is more preferably 30% by mass or more, and further preferably 40% by mass or more. The modification rate of the rubber composition of the present embodiment can be controlled within the above numerical range by adjusting the amount of modifier added to the rubber-like polymer constituting the rubber composition and the modification process time.
[0028] In the rubber composition of the present embodiment, from the viewpoint of dispersibility of silica when a tire is produced from a material using silica, the modification rate of a rubber-like polymer having a molecular weight of 350,000 or more as measured by a GPC method is preferably 40% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. In this specification, when the modification of the rubber-like polymer is nitrogen modification, the "(nitrogen) modification rate" represents the mass ratio of the polymer having a nitrogen atom-containing functional group to the total amount of the rubber composition. The position at which the nitrogen atom is introduced into the rubbery polymer having a molecular weight of 350,000 or more in the rubber composition of this embodiment may be any of the polymerization initiation terminal of the rubbery polymer, the molecular chain (including the graft product), and the polymerization terminal.
[0029] When the rubber-like polymer having a molecular weight of 350,000 or more constituting the rubber composition of this embodiment is a hydrogenated product of a conjugated diene monomer, from the viewpoints of polymerization productivity and high modification rate, and of wear resistance and fuel economy when made into a tire, it is preferable to apply a method in which a nitrogen atom is introduced into the rubber-like polymer using a modifier having a coupling effect containing a nitrogen atom to obtain a modified rubber-like polymer having a molecular weight of 350,000 or more. In this specification, the term "modifier having a coupling effect" refers to a compound which contains the above-mentioned nitrogen element and is capable of reacting with a rubber-like polymer.
[0030] As the modifier having a coupling effect, from the viewpoints of polymerization productivity and a high modification rate, an isocyanate compound, an isothiocyanate compound, an isocyanuric acid derivative, a nitrogen group-containing carbonyl compound, a nitrogen group-containing vinyl compound, a nitrogen group-containing epoxy compound, a nitrogen group-containing alkoxysilane compound, or the like is preferred. As these modifiers having a coupling effect, nitrogen-group-containing alkoxysilane compounds are more preferred from the viewpoints of polymerization productivity of rubber-like polymers having a molecular weight of 350,000 or more, obtaining a high modification rate, and tensile strength when made into tires.
[0031] Examples of the nitrogen group-containing alkoxysilane compound include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacyclohexane, and the like. )-1-aza-2-silacycloheptane, 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy,2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy,2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane Clopentane, 2-methoxy, 2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, and 2-ethoxy, 2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine Amines, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, and tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, and N 1 -(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N 1 -Methyl-N 3 -(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N 3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine, 3-(4-methylpiperazin-1-yl)propyltriethoxysilane.
[0032] When the rubber-like polymer having a molecular weight of 350,000 or more that constitutes the rubber composition of this embodiment is produced by copolymerizing ethylene and a conjugated diene monomer, the rubber composition of this embodiment has the advantage that the amount of metal contained therein can be easily controlled to a desired value. In addition, from the viewpoint of fuel economy, abrasion resistance, and flexibility when the rubber composition of this embodiment is used in a tire, it is preferable that the rubber-like polymer having a molecular weight of 350,000 or more contains at least one of a tin atom, a nitrogen atom, and a silicon atom. From the viewpoint of productivity of rubber-like polymers having a molecular weight of 350,000 or more, a method of introducing a coupling agent containing a tin atom, a nitrogen atom or a silicon atom when the conversion rate of the polymerization reaction reaches 100% is preferred. Examples of coupling agents containing a tin atom, a nitrogen atom, or a silicon atom include, but are not limited to, tin-containing compounds such as bis(1-octadecylmaleate)dioctyltin, isocyanate compounds such as 4,4-diphenylmethane diisocyanate, and alkoxysilane compounds such as glycidylpropyltrimethoxysilane.
[0033] The rubber-like polymer having a molecular weight of 5,000 to less than 350,000 constituting the rubber composition of the present embodiment preferably has a functional group having a high affinity with the reinforcing material from the viewpoint of dispersibility of the reinforcing material when processing a tire composition using the rubber composition. For example, when manufacturing a tire using a material in which the rubber composition of the present embodiment contains silica, the functional group of the rubber-like polymer is preferably, but not limited to, an alkoxysilyl group, an amino group, an epoxy group, a hydroxyl group, a carboxyl group, a nitro group, a mercapto group, etc. More preferably, it is an alkoxysilyl group or an amino group. Hereinafter, in this specification, a compound having elements other than carbon and hydrogen elements will be referred to as a "functionalizing agent." When a modifying agent is used as a functionalizing agent, the modification rate of the rubber-like polymer having a molecular weight of 5,000 to less than 350,000 is preferably 40% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, from the viewpoint of fuel saving. The modification rate of the rubber-like polymer having a molecular weight of 5,000 to less than 350,000 can be calculated by the method described in the examples below. In the method of introducing a functional group into a rubber-like polymer having a molecular weight of 5,000 to less than 350,000, from the viewpoint of polymerization productivity, it is preferable to react the active end of the rubber-like polymer with a functionalizing agent. The functionalizing agent may have a coupling effect, but in the case of coupling, in order to keep the molecular weight within the range, it is necessary to add a large amount of polymerization initiator, which is not preferable from the viewpoint of cost. Therefore, in the method of introducing a functional group into a rubber-like polymer having a molecular weight of 5,000 to less than 350,000, it is preferable to use a functionalizing agent that does not have a coupling function, or to add the amount of the functionalizing agent that has a coupling function at a molar ratio equal to or greater than that of the active polymerization end.
[0034] Examples of functionalizing agents include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza- 2-Silacycloheptane, 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy,2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclo Pentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine Amines, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, N 1 -(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N 1 -Methyl-N 3 -(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N 3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine, 1-butyl-2-pyrrolidone, 1-cyclohexyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, 1,3,4,6-tetrakis(methoxymethyl)glycoluril, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, dihydro-2,5-furandione, 2,2-dimethylsuccinic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 4-methylcyclohexane-1,2-dicarboxylic anhydride, 4-cyclohexene-1,2-dicarboxamide Examples of the silane derivatives include carboxylic acid anhydride, phthalic anhydride, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, trimethoxymethylsilane, ethyltrimethoxysilane, vinyltrimethoxysilane, triethoxymethylsilane, trimethoxypropylsilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, dimethoxydimethylsilane, dimethoxymethylvinylsilane, diethoxydimethylsilane, diethoxymethylvinylsilane, diethoxydiethylsilane, 1,2-epoxycyclohexane, and 1,2-epoxydecane.
[0035] <Silicon content of rubber composition> The rubber composition of the present embodiment preferably has a silicon content of 50 ppm or more. When the silicon content is 50 ppm or more, the interaction between the rubber and the reinforcing material is strengthened, and excellent tensile strength is obtained. The silicon content of the rubber composition is more preferably 100 ppm or more, and further preferably 150 ppm or more. The silicon content of the rubber composition can be controlled within the above range by the amount of silicon-containing coupling agent added.
[0036] <Mooney Relaxation Rate (MSR)> The rubber composition of this embodiment has a Mooney relaxation rate measured at 100°C of preferably 0.7 or less, more preferably 0.6 or less, and even more preferably 0.5 or less, from the viewpoint of good processability when the rubber composition is used for processing. The Mooney relaxation rate is an index of molecular entanglement in a rubber-like polymer; the lower the rate, the greater the degree of molecular entanglement. The Mooney relaxation rate can be reduced by increasing the molecular weight of the rubber-like polymer constituting the rubber composition, increasing the degree of branching with the above-mentioned coupling agents or branching agents, or reducing the amount of rubber softener added to increase the Mooney viscosity. The Mooney relaxation rate was determined by preheating the rubber composition at 100°C for 1 minute, rotating the rotor at 2 rpm, and calculating the Mooney viscosity (ML) from the torque after 4 minutes. (1+4) ) is measured, the rotation of the rotor is immediately stopped and the torque is recorded every 0.1 seconds for 1.6 to 5 seconds after the rotor has stopped in Mooney units. The torque versus time (seconds) is plotted logarithmically to determine the slope of the line, and the absolute value of this slope is used to determine the Mooney relaxation rate. More specifically, it can be measured by the method described in the Examples below.
[0037] <Glass transition temperature> From the viewpoint of tensile strength when made into a tire, the rubber composition of the present embodiment has a glass transition temperature of preferably -90°C or higher, more preferably -80°C or higher, and even more preferably -75°C or higher. On the other hand, from the viewpoints of the cut resistance of the sheet during tire production and the flexibility of the tire when made into a tire, the temperature is preferably -15°C or lower, more preferably -30°C or lower, and even more preferably -40°C or lower. The glass transition temperature is measured in accordance with ISO 22768:2006 by recording a DSC curve while increasing the temperature within a specified temperature range, and the peak top (inflection point) of the DSC differential curve is taken as the glass transition temperature. The glass transition temperature of the rubber composition of the present embodiment can be controlled by adjusting the composition ratio of the vinyl aromatic compound and the conjugated diene compound in the rubber-like polymer constituting the rubber composition, and the iodine value. The method for controlling the glass transition temperature is not particularly limited, but for example, the glass transition temperature can be increased by increasing the composition ratio of the vinyl aromatic compound, and the glass transition temperature can be increased by increasing the composition ratio of the 1,2-bond in the conjugated diene compound. More specifically, when the content of the vinyl aromatic monomer unit in the polymer is 20 mass% or more, the glass transition temperature can be increased to -50°C or higher by setting the iodine value to about 38 to 94. On the other hand, when the iodine value is set to 110, the glass transition temperature can be made to be −50° C. or higher by making the content of the vinyl aromatic monomer unit 20% by mass or higher.
[0038] <Mooney viscosity> The Mooney viscosity of a rubber-like polymer or a rubber composition is an index containing information such as molecular weight, molecular weight distribution, degree of branching, and content of a softener. The Mooney viscosity of the rubber composition of this embodiment measured at 100°C is preferably 50 or more, more preferably 70 or more, and even more preferably 90 or more, from the viewpoints of abrasion resistance, handling stability, and breaking strength when the rubber composition for crosslinking is used in a tire. On the other hand, from the viewpoints of productivity of the rubber composition of this embodiment and processability when the composition is compounded with a filler or the like, it is preferably 200 or less, more preferably 150 or less, even more preferably 130 or less, and even more preferably 110 or less. The Mooney viscosity can be measured by the method specified in ISO289. The Mooney viscosity of the rubber composition can be controlled by adjusting the amount of polymerization initiator added and the amount and type of functionalizing agent having a coupling function added.
[0039] <Rubber softener> The rubber composition of the present embodiment may contain a rubber softener as necessary. The content of the rubber softener is preferably 30% by mass or less. In the rubber composition of the present embodiment, the amount of rubber softener added is preferably 1 to 30% by mass in order to improve processability when inorganic fillers and the like are blended during tire production. When the molecular weight of the rubber-like polymer constituting the rubber composition is high, for example when the weight average molecular weight exceeds 1 million, it is preferable to add 15 to 30 mass% of the rubber softener. On the other hand, from the viewpoint of expanding the degree of freedom of blending when making a composition blended with a filler, it is preferable to add 1 to 15 mass% of the rubber softener. The content of the rubber softener in the rubber composition of this embodiment is more preferably 20% by mass or less, even more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of suppressing deterioration over time when made into a tire.
[0040] The rubber softener is not particularly limited, but examples thereof include extender oils, low molecular rubber polymers, resins, etc., and from the viewpoints of processability, productivity, and economy, extender oils are preferred. Also, from the viewpoint of the abrasion resistance of the tire composition, low molecular rubber polymers that can contribute to crosslinking are preferred. The method of adding a rubber softener to the rubber composition of the present embodiment is not limited to the following, but a preferred method is to add a rubber softener to a polymer solution, mix, and remove the solvent from the resulting polymer solution containing the rubber softener.
[0041] Preferred extender oils include, but are not limited to, aromatic oils, naphthenic oils, paraffinic oils, and the like. Among these, from the viewpoints of environmental safety, oil bleeding prevention, and wet grip properties, aromatic alternative oils having a polycyclic aromatic (PCA) content of 3 mass% or less according to the IP346 method are preferred. Examples of aromatic alternative oils include TDAE (Treated Distillate Aromatic Extracts), MES (Mild Extraction Solvate), and RAE (Residual Aromatic Extracts) shown in Kautschuk Gummi Kunststoffe 52(12)799(1999).
[0042] <Other additives> The rubber composition of the present embodiment may contain various additives such as an antioxidant, if necessary.
[0043] [Method for producing rubber composition] The rubber composition of the present embodiment and the rubber-like polymer constituting the rubber composition are preferably produced by anionic polymerization from the viewpoint of easy control of the molecular structure, and a part or most of the double bonds in a conjugated diene-based polymer obtained by polymerizing or copolymerizing at least a conjugated diene monomer may be hydrogenated (hydrogen added).
[0044] Regarding the rubber composition of this embodiment and the method for producing the rubber-like polymer constituting the rubber composition, examples of the production method that does not hydrogenate (hydrogenate) a part or most of the double bonds in a conjugated diene-based polymer obtained by polymerizing at least a conjugated diene monomer or copolymerizing it with other monomers described later include the coordination polymerization methods described in WO 2019 / 078083, WO 2019 / 111496, WO 2019 / 142501, WO 2019 / 171679, and WO 2019 / 216100. On the other hand, examples of the method of polymerizing or copolymerizing a conjugated diene monomer and then hydrogenating it include, for example, WO 96 / 05250, JP 2000-053706, WO 2003 / 085010, WO 2019 / 151126, WO 2019 / 151127, WO 2002 / 002663, and WO 2015 / 006179. As described above, a conjugated diene monomer is polymerized by anionic polymerization under various additives and conditions, and then copolymerized with other monomers as necessary and then hydrogenated. In these, it is preferable that the vinyl aromatic monomer, ethylene, α-olefin, conjugated diene monomer, and other monomers added during polymerization are the same. The above polymerization step and hydrogenation step may each be carried out in a batchwise or continuous manner.
[0045] Conjugated diene monomers include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-heptadiene. Among these, from the viewpoint of industrial availability, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These may be used alone or in combination of two or more.
[0046] The other monomer is not particularly limited, but from the viewpoint of mechanical strength of a tire formed therefrom, it is preferable to use a vinyl aromatic monomer. Examples of vinyl aromatic monomers include, but are not limited to, styrene, p-methylstyrene, α-methylstyrene, vinylethylbenzene, vinylxylene, vinylnaphthalene, diphenylethylene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethyl ether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, and tertiary amino group-containing diphenylethylene (e.g., 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene). Among these, styrene is preferred from the viewpoint of industrial availability. These may be used alone or in combination of two or more.
[0047] In addition to the above vinyl aromatic monomers, other monomers may be used as necessary. Examples of other monomers include, but are not limited to, unsaturated carboxylic acid esters, unsaturated carboxylic acids, α,β-unsaturated nitrile compounds, α-olefins (butylene, propylene, butylene, pentene, hexene, etc.), ethylene, myrcene, ethylidene norbornene, isopropylidene norbornene, cyclopentadiene, and divinylbenzene.
[0048] <Branching process> In the process for producing the rubber composition of the present embodiment, a step of adjusting the branching degree of the rubber polymer constituting the rubber composition may be carried out. Methods for increasing the branching degree of rubber-like polymers include, in addition to the above-mentioned coupling agents, a method of using, as necessary, a compound derived from a vinyl monomer containing an alkoxysilyl group and / or a halosilyl group (hereinafter referred to as a branching agent) as described below. The vinyl monomer containing an alkoxysilyl group and / or a halosilyl group is not particularly limited, but examples thereof include compounds represented by the following formula (1) or formula (2). The branching agent is added during the polymerization step, and then the monomer is added to continue the polymerization, so that the polymer chains branched at the branching points can be extended. Then, the above-mentioned modifying agent, coupling agent, etc. may be added to carry out the modification step.
[0049] [ka]
[0050] (In formula (1), R 1 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, R 2 and R 3 each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, X 1 each independently represents a halogen atom, m represents an integer of 0 to 2, n represents an integer of 0 to 3, l represents an integer of 0 to 3, and (m+n+l) is 3.
[0051] [ka]
[0052] (In formula (2), R 2 ~R 5 each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, X 2 ~X 3 each independently represents a halogen atom, m represents an integer of 0 to 2, n represents an integer of 0 to 3, l represents an integer of 0 to 3, and (m+n+l) is 3; a represents an integer of 0 to 2, b represents an integer of 0 to 3, c represents an integer of 0 to 3, and (a+b+c) is 3.
[0053] When these branching agents are used, the branching points formed by the moieties derived from the vinyl monomers containing alkoxysilyl groups and / or halosilyl groups are: 29 These branching points can be detected by Si-NMR. More specifically, 29 In Si-NMR, peaks due to branched structures are observed in the range of -45 ppm to -65 ppm, more specifically in the range of -50 ppm to -60 ppm.
[0054] <Method for adjusting peak top molecular weight of rubber composition> The rubber composition of the present embodiment has at least one peak at a molecular weight of 350,000 or more in GPC analysis, and also has at least one peak at a molecular weight of 5,000 or more and less than 350,000. The method for adjusting the molecular weight in the rubber composition of the present embodiment is not particularly limited, but examples thereof include a method of solution blending two or more types of rubbery polymers, a method of adding two or more types of functionalizing agents with different numbers of branches to active polymerization ends, and a method of adding a functionalizing agent or a polymerization initiator to a reactor before all the raw materials are consumed during polymerization of the rubbery polymer. From the viewpoint of productivity of the rubber composition, a method of adding two or more kinds of functionalizing agents having different branch numbers to the active polymerization terminal is preferable, and from the viewpoint of ease of adjusting the molecular weight of the rubber composition, a method of solution blending two or more kinds of rubber-like polymers is preferable.
[0055] <Processes subsequent to the polymerization process of the rubber-like polymer constituting the rubber composition> In the process for producing the rubber composition of this embodiment, it is preferable to carry out a step of adding a functionalizing agent, a polymerization deactivating agent, a neutralizing agent, etc. after the step of polymerizing the rubber-like polymer that constitutes the rubber composition. The polymerization deactivator is not limited to the following, but examples thereof include water and alcohols such as methanol, ethanol, and isopropanol. When a branching agent is not added during the polymerization of the rubber-like polymer, a step of adding a coupling agent after the polymerization step of the rubber-like polymer is essential. The coupling agent can impart a branched structure to the rubber-like polymer by adding it when the polymerization reaction is completed and the activity of the polymer growing end is maintained. When a coupling agent containing a functional group in the residue is used as the coupling agent, it is possible to form branches in the coupling reaction and simultaneously modify the polymer. Examples of neutralizing agents include, but are not limited to, carboxylic acids such as stearic acid, oleic acid, and versatic acid (a highly branched carboxylic acid mixture having 9 to 11 carbon atoms, with the majority having 10 carbon atoms); aqueous solutions of inorganic acids, and carbon dioxide gas.
[0056] After the polymerization step of the rubber-like polymer constituting the rubber composition of the present embodiment, it is preferable to add a rubber stabilizer from the viewpoints of preventing gel formation and improving processing stability. The rubber stabilizer is not limited to the following ones, and known ones can be used. For example, preferred ones include antioxidants such as 2,6-di-tert-butyl-4-hydroxytoluene (hereinafter also referred to as "BHT"), n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenol) propionate, and 2-methyl-4,6-bis[(octylthio)methyl]phenol.
[0057] After the polymerization step of the rubber-like polymer constituting the rubber composition of the present embodiment, a rubber softener may be added as necessary.
[0058] After the polymerization step of the rubber-like polymer constituting the rubber composition of the present embodiment, various additives may be further added as necessary. The additives may be added as a master batch in a process before molding, such as fillers and resin components as tackifiers, as described below. In this case, the amount of the additive is preferably 15% by mass or less.
[0059] <Step of Removing Solvent from Polymerization Solution of Rubber-like Polymer Constituting Rubber Composition> In the method for producing the rubber composition of this embodiment, examples of a method for removing the solvent from the polymer solution of the rubber-like polymer include methods that utilize flashing, steam stripping, a drying conveyor after dehydration, a devolatilizing extruder, a drum dryer, and a devolatilizing kneader. From the viewpoint of small thermal history, a method using at least steam stripping is preferred. Examples of steam stripping and treatment methods before and after the steam stripping include those described in JP-A-10-168101, JP-A-10-204136, WO 2013-146530, and JP-A-2019-131810. In the method for producing the rubber composition of this embodiment, it is preferable to carry out, before the extrusion drying step, a solvent removal step in which the solvent is removed from the polymer solution by steam stripping, and a screening step in which the stripping water is separated from the polymer slurry and water-containing crumbs are taken out. Also, a flashing step may be performed prior to steam stripping to increase the solution concentration. Prior to the extrusion drying step, a desolvation step is carried out in which the solvent is removed from the rubber polymer solution by steam stripping, thereby obtaining a solvent-free slurry in which porous, granular crumbs containing moisture are dispersed in hot water. By carrying out a screening step in which stripping water is separated from the rubber polymer slurry to extract water-containing crumbs, porous granular crumbs containing water can be obtained. If necessary, it is preferable to carry out a squeezing and dehydrating step in which dehydration is performed using a roll, a screw compression squeezer, etc. By using these dehydrating steps, it is possible to obtain hydrous crumbs with a lower moisture content prior to the extrusion drying step.
[0060] From the viewpoint of odor and VOC reduction, the residual solvent content of the rubber composition of the present embodiment is preferably low, and is preferably 5000 ppm or less, more preferably 3000 ppm or less, and even more preferably 1500 ppm or less. From the viewpoint of economic balance, the residual solvent content is preferably 50 ppm or more, more preferably 150 ppm or more, and even more preferably 300 ppm or more. The water content in the rubber composition of the present embodiment is preferably 0.05% by mass or more and 1.5% by mass or less. From the viewpoint of suppressing gel formation during drying after solvent removal, the water content in the rubber composition is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. On the other hand, from the viewpoint of suppressing condensation and discoloration resistance in the rubber composition, the water content is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.8% by mass or less.
[0061] [Method for producing rubber composition molded article] The method for producing a rubber composition molded article of the present embodiment includes a step of producing the rubber composition of the present embodiment and a step of molding using the rubber composition. The rubber composition to be molded may be a crosslinkable rubber composition containing a crosslinking agent, as described below.
[0062] The rubber composition can be produced by the steps of polymerizing a rubbery polymer A having a peak top at a molecular weight of 350,000 or more, polymerizing a rubbery polymer B having a peak top at a molecular weight of 5,000 to less than 350,000, mixing the rubbery polymer A and the rubbery polymer B in a solution to obtain a mixed solution, and removing the solvent from the mixed solution.
[0063] The rubber composition may also be produced by a process comprising the steps of polymerizing, in a single reactor, a rubbery polymer A having a peak top at a molecular weight of 350,000 or more, polymerizing a rubbery polymer B having a peak top at a molecular weight of 5,000 to less than 350,000, and adding two or more types of functionalizing agents having different degrees of branching to each of the rubbery polymer A and the rubbery polymer B to functionalize the polymer chain ends, and removing the solvent from the polymerization solution.
[0064] (Method for molding rubber composition molded article) From the viewpoint of handling, the rubber composition molded article of the present embodiment is preferably a sheet-like or block-like molded article. A block-like molded article is more preferable, and a molded article having a length of 1,000 cm or less is more preferable. 3 The above block-shaped bales are more preferred. A rectangular bales weighing 17.5 kg to 35 kg is even more preferred. The molding method is to make a material with a specific surface area of 0.7 m 2 / g~3.2m 2 In the present invention, a method is preferred in which crumbs of a rubber composition having a viscosity of 1 / g are prepared and the crumbs are compression molded. From the viewpoint of moldability, the method preferably further includes a step of sieving the crumbs before molding. When the crumbs of the rubber composition are compression molded, the crumbs may also adhere to each other, so the specific surface area of the molded product is lower than that of the crumbs. The adhesion of the crumbs during compression molding can be adjusted by the molecular weight, composition, and structure of the rubber-like polymer, the rubber softener composition, and the temperature and pressure during compression. For example, if you want to increase the adhesion of the crumbs and decrease the specific surface area of the veil, it is preferable to select conditions such as decreasing the molecular weight of the rubber-like polymer, increasing the amount of the rubber softener, and increasing the temperature and pressure during compression.
[0065] The specific surface area of the rubber composition molded product is preferably 0.005 to 0.05 m 2 / g, and more preferably, from the viewpoint of film packaging properties, 0.01 to 0.04 m 2 / g. The specific surface area of the molded product is 0.005 m 2 / g or more, the expansion of the veil is suppressed, and the specific surface area of the compact is 0.05 m 2 / g or less, peeling of crumbs from the green body is reduced. The specific surface area of the molded body can be determined by the BET method. Generally, since the specific surface area of a large-sized molded body may vary depending on the location, it is preferable to collect from near the center of the molded body. Before molding, the crumbs are preferably sieved according to particle size and then mixed in an appropriate ratio. If the specific surface area of a molded body formed using the crumbs after solvent removal exceeds the upper limit of the above range, the composition of large crumbs among the sieved crumbs should be increased and the composition of small crumbs should be decreased; if the specific surface area does not reach the lower limit, the composition of large crumbs should be decreased and the composition of small crumbs should be increased.
[0066] The molding compression pressure for the molded body is preferably 3 to 40 MPa, and more preferably 10 to 25 MPa. When the compression pressure during molding is 30 MPa or less, the equipment can be designed compactly and the installation efficiency is good, while when the compression pressure during molding is 3 MPa or more, the moldability is good. When the moldability is good, the surface of the molded product is smooth, there is no peeling of the polymer after the molding process, and expansion after molding tends to be suppressed. The temperature of the rubber polymer during molding is preferably 30 to 140° C., and more preferably 50 to 100° C. from the viewpoints of reducing residual solvent and suppressing thermal degradation. When the temperature of the rubber composition during molding is 30° C. or higher, moldability is good, while when the temperature is 140° C. or lower, gel formation due to thermal degradation of the rubber composition is suppressed, which is preferable. The higher the temperature and pressure during molding, the smaller the specific surface area of the bale. The pressure retention time during compression is preferably 3 to 30 seconds, more preferably 5 to 20 seconds. When the pressure retention time during compression is 30 seconds or less, production efficiency is good, and when it is 5 seconds or more, moldability is good.
[0067] In order to prevent the molded bodies from sticking to each other, it is preferable to wrap them in a resin film (wrapping sheet). Examples of the resin for the film include polyethylene, ethylene copolymer resin, polystyrene, high impact polystyrene, and PET. From the viewpoints of ease of handling during transportation of the molded article and of preventing condensation from forming in the gap between the packaging sheet and the bale, it is preferable that the packaging sheet has high adhesion.
[0068] The rubber composition molded body is stored in a container for transportation. If the expansion rate of the molded article one day after molding is less than 5%, the molded article will have good storage properties in a container, which is preferable.
[0069] (Other components that can be contained in rubber composition and rubber composition molded article) From the viewpoint of higher mechanical strength and the like, a crosslinking agent may be added to the rubber composition molded article of this embodiment to prepare a crosslinkable rubber composition, which may then be crosslinked and used in various applications as a crosslinked article. Moreover, the rubber composition, the rubber composition for crosslinking, and the rubber composition molded article of the present embodiment may further contain other rubbers, fillers, crosslinking agents, and the like, as necessary.
[0070] The other rubbers are not particularly limited and can be appropriately selected according to the purpose. For example, styrene-butadiene rubber (emulsion polymerization tire or solution polymerization type), natural rubber, polyisoprene, butadiene rubber (high cis polybutadiene, low cis polybutadiene, syndiotactic 1,2-polybutadiene, acrylonitrile-butadiene rubber (NBR), chloroprene rubber, ethylene-propylene rubber (EPM) and other ethylene-α-olefin copolymer rubbers, ethylene-propylene-diene rubber (EPDM), butyl rubber, polysulfide rubber, silicone rubber, fluororubber, urethane rubber, and rubber-like copolymers having an iodization of 10 to 270, an ethylene structure amount of 3 mass% or more, and a vinyl aromatic monomer block of 10 mass% or less, which are different from the rubber composition of the present embodiment, can be mentioned. These may be used alone or in combination of two or more. The mixing may be performed by mixing a dry polymer after polymerization or by mixing in a solution state during polymerization.
[0071] From the viewpoints of tensile strength and tensile elongation, at least the tire composition molded article using the rubber composition of this embodiment preferably contains 3 to 40 parts by mass of resin per 100 parts by mass of the rubber component in the rubber composition. From the viewpoint of tensile energy, it is more preferable that the amount is 5 parts by mass or more, and even more preferable that the amount is 10 parts by mass or more. On the other hand, from the viewpoint of ease of mixing the rubber composition, it is more preferable that the amount is 30 parts by mass or less, and even more preferable that the amount is 25 parts by mass or less. Resins are compounds that are solid at room temperature (23° C.) and are essentially based on carbon and hydrogen (but may also contain other atoms). The resins may be aliphatic, cycloaliphatic, aromatic, hydrogenated aromatic, aliphatic / aromatic which may be based on aliphatic and / or aromatic monomers. The resins may be petroleum or non-petroleum based natural or synthetic resins. The resin may be a hydrocarbon resin selected from the group consisting of a homopolymer or copolymer resin of cyclopentadiene (CPD), a homopolymer or copolymer resin of dicyclopentadiene (DCPD), a homopolymer or copolymer resin of terpene, a homopolymer or copolymer resin of a C5 fraction, a homopolymer or copolymer resin of a C9 fraction, a homopolymer or copolymer resin of α-methylstyrene, and blends of these resins. More specifically, among the above copolymer resins, a copolymer selected from the group consisting of (D)CPD / vinyl aromatic copolymer resin, (D)CPD / terpene copolymer resin, terpene / phenol copolymer resin, (D)CPD / C5 fraction copolymer resin, (D)CPD / C9 fraction copolymer resin, terpene / vinyl aromatic copolymer resin, terpene / phenol copolymer resin, C5 fraction / vinyl aromatic copolymer resin, and blends of these resins is preferred. The resin may be used alone or in combination of two or more kinds. From the viewpoints of tensile strength and tensile elongation, the resin preferably has a glass transition temperature of 30° C. or higher, and more preferably 40° C. or higher. On the other hand, from the viewpoint of ease of mixing the rubber composition for crosslinking, the glass transition temperature is preferably 100° C. or lower, and more preferably 80° C. or lower.
[0072] A tire composition containing the rubber composition of the present embodiment may contain a filler from the viewpoint of improving reinforcement properties. The amount of the filler to be mixed is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 to 130 parts by mass, and more preferably 30 to 90 parts by mass, per 100 parts by mass of the rubber component. The rubber component herein includes the above-mentioned other rubbers in addition to the rubber-like polymer constituting the composition of the present embodiment. When the amount of filler is 10 parts by mass or more, the effect of improving reinforcing properties can be obtained by blending the filler, and by making the amount 130 parts by mass or less, a significant decrease in fuel efficiency when made into a tire can be avoided while maintaining good workability. Examples of the filler include carbon black, silica, aluminum hydroxide, clay, alumina, talc, mica, kaolin, glass balloons, glass beads, calcium carbonate, magnesium carbonate, magnesium hydroxide, magnesium oxide, titanium oxide, potassium titanate, barium sulfate, etc., and among these, carbon black is preferably used. These may be used alone or in combination of two or more. The carbon black is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include FEF, GPF, SRF, HAF, N339, IISAF, ISAF, SAF, etc. These may be used alone or in combination of two or more kinds. The nitrogen adsorption specific surface area (N2SA, measured in accordance with JIS K6217-2:2001) of the carbon black is not particularly limited and can be appropriately selected depending on the purpose. Among these fillers, silica is preferred from the viewpoints of fuel economy and wet skid resistance when the rubber composition for crosslinking is made into a tire tread, and precipitated silica is more preferred. The amount of silica added to the crosslinkable rubber composition of the present embodiment is preferably 40 to 120 parts by mass, more preferably 50 to 100 parts by mass, and further preferably 60 to 80 parts by mass, per 100 parts by mass of the rubber component, from the viewpoints of fuel saving and wet skid resistance.
[0073] The rubber composition, the rubber composition for crosslinking, and the molded article of the rubber composition of the present embodiment may contain a silane coupling agent from the viewpoints of improving the dispersibility of the filler and the tensile strength of the crosslinked article. The silane coupling agent has the function of strengthening the interaction between the rubber component and the inorganic filler, and has groups that have affinity or binding properties for both the rubber component and the filler. A compound having a sulfur bonding portion and an alkoxysilyl group or silanol group portion in one molecule is preferred. Such compounds include, but are not limited to, for example, bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, bis-[2-(triethoxysilyl)-ethyl]-tetrasulfide, S-[3-(triethoxysilyl)-propyl]octanethioate and condensates of S-[3-(triethoxysilyl)-propyl]octanethioate with [(triethoxysilyl)-propyl]thiol, silanes bearing at least one thiol (-SH) functional group (referred to as mercaptosilane) and / or at least one masked thiol group. The content of the silane coupling agent in the tire composition is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 20 parts by mass or less, and even more preferably 1.0 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the above-mentioned filler. When the content of the silane coupling agent is within the above range, the above-mentioned addition effect of the silane coupling agent tends to be more remarkable.
[0074] [Rubber composition for crosslinking] The rubber composition for crosslinking according to the present embodiment is The rubber composition of the present embodiment and a crosslinking agent are contained, and the crosslinking agent is contained in an amount of 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the rubber component. The rubber component includes the above-mentioned other rubbers in addition to the rubber-like polymer constituting the composition of the present embodiment. The crosslinking agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the crosslinking agent include sulfur-based crosslinking agents, organic peroxide-based crosslinking agents, inorganic crosslinking agents, polyamine crosslinking agents, resin crosslinking agents, sulfur compound-based crosslinking agents, and oxime-nitrosamine-based crosslinking agents, and these may be used in combination. Among these, sulfur-based crosslinking agents (vulcanizing agents) are more preferable for use in rubber compositions for tires, and sulfur is particularly preferable.
[0075] The content of the crosslinking agent in the rubber composition for crosslinking is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the rubber component, and from the viewpoints of high tensile strength and fast crosslinking speed, it is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.5 parts by mass or more. On the other hand, from the viewpoints of suppressing uneven crosslinking and high tensile strength, it is preferably 20 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. In the rubber composition for crosslinking, a vulcanization accelerator may be used in addition to the vulcanizing agent. Examples of the vulcanization accelerator include guanidine-based, aldehyde amine-based, aldehyde ammonia-based, thiazole-based, sulfenamide-based, thiourea-based, thiuram-based, dithiocarbamate-based, and xanthate-based compounds.
[0076] In addition, the crosslinking rubber composition may contain various additives such as other softeners, fillers, heat stabilizers, antistatic agents, weather stabilizers, antioxidants, colorants, and lubricants, in addition to those mentioned above. As the other softeners, known softeners can be used. As the other fillers, for example, calcium carbonate, magnesium carbonate, aluminum sulfate, and barium sulfate can be mentioned. As the above-mentioned heat stabilizers, antistatic agents, weather stabilizers, antioxidants, colorants, and lubricants, known materials can be used respectively.
[0077] (Method of kneading crosslinking composition) The method of mixing the rubber component, the silica-based inorganic filler, the carbon black and other fillers, the silane coupling agent, the rubber softener, and other additives is not limited to the following, but includes, for example, a melt-kneading method using a general mixer such as an open roll, a Banbury mixer, a kneader, a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, and a method of dissolving and mixing each component and then removing the solvent by heating. Among these, the melt-kneading method using a roll, a Banbury mixer, a kneader, or an extruder is preferred from the viewpoints of productivity and good kneading. In addition, both a method of kneading the rubber component, the other fillers, the silane coupling agent, and the additives at once, and a method of mixing them in several batches can be applied.
[0078] [Application] The rubber composition of the present embodiment can be used, preferably as a crosslinkable rubber composition, for tire components, interior and exterior parts of automobiles, anti-vibration rubber, belts, footwear, foams, various industrial goods, and the like. Among these, it is preferably used for tire parts. As tire components, the material can be used in various tire parts such as fuel-efficient tires, all-season tires, high-performance tires, snow tires, studless tires, etc., including tire treads, carcasses, sidewalls, beads, etc. In particular, as tire components, the material has an excellent balance of wear resistance, fuel efficiency, wet skid resistance, and snow performance when vulcanized, and is therefore suitably used for tire treads of fuel-efficient tires, high-performance tires, and snow tires. A conventional method can be used for manufacturing a tire. For example, at least one carcass layer selected from the group consisting of an unvulcanized rubber composition for crosslinking and a cord, a belt layer, a tread layer, and other components normally used in tire manufacturing are laminated on a tire building drum, and the drum is removed to obtain a green tire. The green tire is then heated and vulcanized according to a conventional method to manufacture a desired tire (e.g., a pneumatic tire). EXAMPLES
[0079] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples, but the present embodiment is not limited in any way to the following examples and comparative examples. Various physical properties in the examples and comparative examples were measured by the methods shown below.
[0080] (Microstructure of butadiene portion of rubber-like polymer before hydrogenation (1,2-vinyl bond content)) As a sample, 50 mg of the rubber-like polymer before hydrogenation was dissolved in 10 mL of carbon disulfide to prepare a measurement sample. Using a solution cell, infrared spectra are recorded from 600 to 1000 cm -1 The absorbance at a predetermined wave number was measured in the range of 100 nm to 150 nm, and the microstructure of the butadiene portion, i.e., the amount of 1,2-vinyl bonds (mol%) was calculated according to the formula of Hampton's method (method described in R.R. Hampton, Analytical Chemistry 21, 923 (1949)) (measuring device: Fourier transform infrared spectrophotometer "FT-IR230" manufactured by JASCO Corporation).
[0081] (Peak Top Molecular Weight (Mp) of Rubber Polymer and Rubber Composition) The chromatogram was measured using a GPC measuring device equipped with three connected columns packed with polystyrene gel, and the peak top molecular weight (Mp) was determined based on a calibration curve using standard polystyrene. The eluent used was THF containing 5 mmol / L triethylamine. The columns used were: guard column: Tosoh Corporation (trade name: "TSKguardcolumn SuperH-H"); and columns: Tosoh Corporation (trade names: "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000"). An RI detector (manufactured by Tosoh Corporation under the trade name "HLC8020") was used under conditions of an oven temperature of 40°C and a THF flow rate of 0.6 mL / min. 10 mg of the sample to be measured was dissolved in 20 mL of THF to prepare a measurement solution, and 20 μL of the measurement solution was injected into the GPC measurement device and measured.
[0082] (Polymer Mooney Viscosity (ML) and Mooney Viscosity Relaxation Rate (MSR) of Rubber-like Polymers and Rubber Compositions) The Mooney viscosity (ML) was measured using a Mooney viscometer (manufactured by Ueshima Seisakusho Co., Ltd., product name "VR1132") in accordance with ISO 289 using an L-shaped rotor. The measurement temperature was 100°C. First, the sample was preheated at the test temperature for 1 minute, and then the rotor was rotated at 2 rpm. The torque was measured after 4 minutes to determine the Mooney viscosity (ML (1+4) ) was decided. After the Mooney measurement, the rotation of the rotor of the Mooney viscometer was stopped, and the decay of the torque applied to the rotor was plotted against the relaxation time in double logarithmic form, and the Mooney viscosity relaxation rate (MSR) was calculated from the slope.
[0083] (Modification rate of rubber polymer and rubber composition) Measurement was performed by column adsorption GPC as follows: The measurement was performed by utilizing the property of the rubber-like polymer modified with a nitrogen atom-containing functional group and the rubber composition to be adsorbed onto a column. The amount of a sample solution containing a sample and low molecular weight internal standard polystyrene was adsorbed onto the silica-based column by measuring the difference between the chromatogram measured using a polystyrene-based column and the chromatogram measured using a silica-based column, and the modification rate was calculated. Specifically, it is as follows: Preparation of sample solution: 10 mg of the sample and 5 mg of standard polystyrene were dissolved in 20 mL of THF to prepare a sample solution. THF containing 5 mmol / L triethylamine was used as the eluent, and 20 μL of the sample solution was injected into the device for measurement. The guard column was Tosoh Corporation's product name "TSKguardcolumn SuperH-H", and the columns were Tosoh Corporation's product names "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000". The chromatogram was obtained by measurement using an RI detector (Tosoh Corporation's HLC8020) under the conditions of a column oven temperature of 40°C and a THF flow rate of 0.6 mL / min. GPC measurement conditions using a silica column: A Tosoh Corporation product name "HLC-8320GPC" was used, THF was used as the eluent, 50 μL of the sample solution was injected into the device, and a chromatogram was obtained using an RI detector under the conditions of a column oven temperature of 40°C and a THF flow rate of 0.5 ml / min. The columns used were Zorbax PSM-1000S, PSM-300S, and PSM-60S, and a guard column "DIOL 4.6 × 12.5 mm 5 micron" was connected to the front of the columns. How to calculate the denaturation rate: The total peak area of the chromatogram using the polystyrene column was set as 100, the peak area of the sample was set as P1, the peak area of the standard polystyrene was set as P2, the total peak area of the chromatogram using the silica column was set as 100, the peak area of the sample was set as P3, and the peak area of the standard polystyrene was set as P4, and the modification rate (%) was calculated using the following formula. Denaturation rate (%) = [1-(P2 x P3) / (P1 x P4)] x 100 (where P1+P2=P3+P4=100)
[0084] (Modification rate of rubber-like polymers and rubber compositions in the range of molecular weight 350,000 or more) The modification ratios of the rubber-like polymer and rubber composition in the region of molecular weight of 350,000 or more were calculated in the same manner as the modification ratio described above, but limited to the region of molecular weight of 350,000 or more. In order to calculate the modification rate in the region of molecular weight of 350,000 or more, a calibration curve was prepared in advance using standard polystyrene by GPC using a silica-based column. Calculation method for the denaturation rate in the region with a molecular weight of 350,000 or more The total peak area of the chromatogram using a polystyrene column was set as 100, the peak area of 350,000 or more in the sample was set as Q1, the peak area of standard polystyrene was set as Q2, the total peak area of the chromatogram using a silica column was set as 100, the peak area of 350,000 or more in the sample was set as Q3, and the peak area of standard polystyrene was set as Q4. The modification rate (%) was calculated using the following formula. Denaturation rate (%) = [1-(Q2 x Q3) / (Q1 x Q4)] x 100 (where Q1+Q2=Q3+Q4=100)
[0085] (Silicon Content of Rubber Polymer and Rubber Composition) The silicon content of the rubber-like polymer and rubber composition samples was measured using an ICP mass spectrometer (Agilnet7700s, manufactured by Agilent Technologies).
[0086] (Iodine Value of Rubber Polymer and Rubber Composition) The iodine value was calculated according to the method described in "JIS K 0070:1992".
[0087] (Bound styrene content, ethylene structure content, α-olefin content, conjugated diene monomer unit content, and hydrogenation rate of rubber-like polymer and rubber composition) Using a rubber-like polymer and a rubber composition as samples, 1 The amount of bound styrene, the amount of ethylene structure, the α-olefin content, the conjugated diene monomer unit, and the hydrogenation rate were measured by H-NMR. 1 The conditions for HNMR measurement are as follows. (Measurement conditions) Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement sample: Rubber block polymer or polymer block Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse Delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃
[0088] (Styrene block content of rubbery polymer and rubber composition) A chain consisting of eight or more styrene structural units is defined as a styrene block, and the styrene block content was calculated as follows. From the 400 MHz 1H-NMR spectrum measured using deuterated chloroform as a solvent, the integral ratio of each chemical shift range of (X) below was determined to determine the content of the styrene block in the rubber block polymer. (X) Aromatic vinyl compounds with 8 or more chains: 6.00≦S<6.68
[0089] (Average shrinkage factor value (g')) Using rubber-like polymers and rubber compositions as samples, a GPC measuring device (manufactured by Malvern under the trade name "GPCmax VE-2001") having three columns packed with polystyrene gel as a packing material was used to measure using three detectors connected in that order: a light scattering detector, an RI detector, and a viscosity detector (manufactured by Malvern under the trade name "TDA305"). Based on the standard polystyrene, the absolute molecular weight was determined from the results of the light scattering detector and the RI detector, and the intrinsic viscosity was determined from the results of the RI detector and the viscosity detector. For linear polymers, the intrinsic viscosity is [η] = -3.927 × M 0.743 was used to calculate the shrinkage factor (g') as the ratio of the intrinsic viscosity corresponding to each molecular weight. The calculated shrinkage factors were averaged in the range of molecular weights of 350,000 or more and in the range of molecular weights of 5,000 to less than 350,000, with the molecular weight of 350,000 as the border, to obtain an average shrinkage factor value. The eluent used was THF containing 5 mmol / L triethylamine. The columns used were "TSKgel G4000HXL", "TSKgel G5000HXL", and "TSKgel G6000HXL" manufactured by Tosoh Corporation. 20 mg of the sample to be measured was dissolved in 10 mL of THF to prepare a measurement solution, and 100 μL of the measurement solution was injected into the GPC measurement device and measured under conditions of an oven temperature of 40° C. and a THF flow rate of 1 mL / min.
[0090] (Degree of branching) The degree of branching of the rubber-like polymer was adjusted as desired by the type of functionalizing agent added after completion of the polymerization, the addition of a branching agent, and the amount of each added. The degree of branching was adjusted by using functionalizing agents with different branching degrees. <Maximum branching degree: 2> 3-(4-Methylpiperazin-1-yl)propyltriethoxysilane (Y in the table) <Maximum branching degree: 4> 2,2-Dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azacylolidine (X in the table) Tetrachlorosilane <Maximum branching degree: 8> Tris(3-trimethoxysilylpropyl)-[3-(2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propanediamine (Z in the table)
[0091] The maximum degree of branching can be achieved when the reactive functional group equivalent during functionalization becomes 1 equivalent for the polymerization active terminal. It is also possible to suppress the degree of branching by adding a functionalizing agent so that the functional group equivalent becomes excessive for the polymerization active terminal.
[0092] (Area ratio (BA) / (AA+BA) in GPC curve) A chromatogram was measured using a GPC measuring device with three columns packed with polystyrene gel connected together, and a molecular weight curve (GPC curve) of the rubber-like polymer and rubber composition was obtained based on a calibration curve using standard polystyrene. In the obtained GPC curve, the area of the region with a molecular weight of 5,000 to 350,000 and the area of the region with a molecular weight of 350,000 or more were designated as BA and AA, respectively, and the desired (BA) / (AA+BA) was calculated.
[0093] [Production of rubber-like polymer] (Preparation of hydrogenation catalyst) In the Production Examples described later, the hydrogenation catalyst used in preparing the rubber polymer was prepared by the following method. <Manufacturing example α> A nitrogen-substituted reaction vessel was charged with 1 liter of dried and purified cyclohexane, and 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. With sufficient stirring, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was allowed to react at room temperature for approximately 3 days to obtain a hydrogenation catalyst (TC-1).
[0094] (Polymerization of rubber-like polymers) <(Production Example 1) Rubber-like Polymer A> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 2,318 g of 1,3-butadiene, 1,290 g of styrene, 25,800 g of cyclohexane, and 1.7 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 1.6 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer observed, an additional 692 g of 1,3-butadiene was added. When the temperature rise in the reactor due to the heat of reaction of the added butadiene had finished, 1.6 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table), which is the first functionalizing agent, was added to the reactor and stirred for 5 minutes. A portion of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. Thereafter, the hydrogenation catalyst (TC-1) prepared in the above <Production Example α> was added to the rubber-like polymer solution before hydrogenation in an amount of 60 ppm (Ti standard) per 100 parts by mass of the rubber-like polymer before hydrogenation, and a hydrogenation reaction was carried out for 50 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C to obtain a rubber-like polymer. The hydrogenation rate of the resulting rubber-like polymer A was 94 mol %. To the resulting rubber polymer solution were added 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol as antioxidants. The analytical values of the rubber polymer A are shown in Table 1.
[0095] <(Production Example 2) Rubber-like Polymer B> A rubber-like polymer B was obtained in the same manner as in the above (Production Example 1), except that the amount of 2,2-di(2-tetrahydrofuryl)propane added was changed to 2.1 g, the amount of n-butyllithium added was changed to 2.0 g, the type of the first functionalizing agent was changed to 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) and the amount added was changed to 7.6 g. The analytical values of the rubber polymer B are shown in Table 1.
[0096] <(Production Example 3) Rubber-like Polymer C> A rubber-like polymer C was obtained in the same manner as in Production Example 1 above, except that the amount of hydrogenation was changed to adjust the hydrogenation rate. The analytical values of the rubbery polymer C are shown in Table 1.
[0097] <(Production Example 4) Rubber-like Polymer D> A rubber-like polymer D was obtained in the same manner as in Production Example 2, except that the amount of hydrogenation was changed to adjust the hydrogenation rate. The analytical values of the rubbery polymer D are shown in Table 1.
[0098] <(Production Example 5) Rubber Polymer E> A rubber-like polymer E was obtained in the same manner as in Production Example 1 above, except that the amount of hydrogenation was changed to adjust the hydrogenation rate. The analytical values of the rubbery polymer E are shown in Table 1.
[0099] <(Production Example 6) Rubber-like Polymer F> A rubber-like polymer F was obtained in the same manner as in Production Example 2 above, except that the amount of hydrogenation was changed to adjust the hydrogenation rate. The analytical values of the rubbery polymer F are shown in Table 1.
[0100] <(Production Example 7) Rubber Polymer G> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 1,720 g of 1,3-butadiene, 1,987 g of styrene, 25,800 g of cyclohexane, and 1.5 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 1.5 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer observed, an additional 593 g of 1,3-butadiene was added. After the temperature rise in the reactor due to the heat of reaction of the added butadiene had finished, 1.6 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table) as the first functionalizing agent was added to the reactor and stirred for 5 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. In the subsequent hydrogenation step, the hydrogenation rate was adjusted in the same manner as in Production Example 1 except for the amount of hydrogen added, to obtain a rubber polymer G. The analytical values of the rubber polymer G are shown in Table 1.
[0101] <(Production Example 8) Rubber-like Polymer H> A rubber-like polymer H was obtained in the same manner as in the above (Production Example 2), except that the amount of the first functionalizing agent, 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table), added was changed to 3.8 g, the amount of hydrogen added was changed, and the hydrogenation rate was adjusted. The analytical values of the rubber polymer H are shown in Table 1.
[0102] <(Production Example 9) Rubber-like Polymer I> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 2,318 g of 1,3-butadiene, 1,290 g of styrene, 25,800 g of cyclohexane, and 1.7 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 1.6 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer observed, an additional 692 g of 1,3-butadiene was added. After the temperature rise in the reactor due to the heat of reaction of the added butadiene had finished, 0.4 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table), which was the first functionalizing agent, was added to the reactor and stirred for 1 minute. Thereafter, 5.9 g of 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) as a second functionalizing agent was added, and the mixture was stirred for 4 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. In the subsequent hydrogenation step, the hydrogenation rate was adjusted in the same manner as in Production Example 1 above, except for the amount of hydrogen added, to obtain a rubber polymer I. The analytical values of the rubbery polymer I are shown in Table 1.
[0103] <(Production Example 10) Rubber-like Polymer J> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 2,318 g of 1,3-butadiene, 1,290 g of styrene, 25,800 g of cyclohexane, and 1.4 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 1.3 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when this increase in temperature was no longer observed, 1.3 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table), which was the first functionalizing agent, was added to the reactor and stirred for 1 minute. An additional 692 g of 1,3-butadiene was then added. After the temperature rise in the reactor due to the heat of reaction of the added butadiene had finished, 4.9 g of 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table), which was a second functionalizing agent, was added to the reactor and stirred for 4 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. The subsequent hydrogenation step was carried out in the same manner as in Production Example 1 except for the amount of hydrogen added, and the hydrogenation rate was adjusted to obtain a rubber polymer J. The analytical values of rubber polymer J are shown in Table 1.
[0104] <(Production Example 11) Rubber Polymer K> A 43 L internal volume autoclave equipped with a stirrer and a jacket and capable of controlling temperature was used as a reactor. 2,318 g of 1,3-butadiene, 1,290 g of styrene, 25,800 g of cyclohexane, and 2.6 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 2.4 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer observed, an additional 692 g of 1,3-butadiene was added. After the temperature rise in the reactor due to the heat of reaction of the added butadiene had finished, 0.7 g of tris(3-trimethoxysilylpropyl)-[3-(2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propanediamine (shown as Z in the table), which was the first functionalizing agent, was added to the reactor and stirred for 1 minute. Thereafter, 9.2 g of 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) as a second functionalizing agent was added, and the mixture was stirred for 4 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. The subsequent hydrogenation step was carried out in the same manner as in Production Example 1 except for the amount of hydrogen added, and the hydrogenation rate was adjusted to obtain a rubber polymer K. The analytical values of rubber polymer K are shown in Table 2.
[0105] <(Production Example 12) Rubber Polymer L> A rubber-like polymer L was obtained in the same manner as in <Production Example 2> above, except that the amount of 2,2-di(2-tetrahydrofuryl)propane added was changed to 5.3 g, the amount of n-butyllithium added was changed to 5.0 g, the amount of the first functionalizing agent 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) added was changed to 45.2 g, and the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubber polymer L are shown in Table 2.
[0106] <(Production Example 13) Rubber Polymer M> A rubber-like polymer M was obtained in the same manner as in <Production Example 1> above, except that the first functionalizing agent was changed to tetrachlorosilane, the amount added was changed to 0.9 g, and the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubber polymer M are shown in Table 2.
[0107] <(Production Example 14) Rubber Polymer N> A rubber-like polymer N was obtained in the same manner as in <Production Example 1> above, except that the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubber polymer N are shown in Table 2.
[0108] <(Production Example 15) Rubber-like Polymer O> A rubber-like polymer O was obtained in the same manner as in <Production Example 2> above, except that the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubber polymer O are shown in Table 2.
[0109] <(Production Example 16) Rubber-like Polymer P> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 4,300 g of 1,3-butadiene, 25,800 g of cyclohexane, and 2.1 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 2.0 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer confirmed, 2.0 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table), which was the first functionalizing agent, was added to the reactor and stirred for 5 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. Thereafter, the hydrogenation catalyst (TC-1) prepared in the above <Production Example α> was added to the rubber-like polymer solution before hydrogenation in an amount of 60 ppm (Ti standard) per 100 parts by mass of the rubber-like polymer before hydrogenation, and a hydrogenation reaction was carried out for 50 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C to obtain a rubber-like polymer. The hydrogenation rate of the resulting rubber-like polymer P was 85 mol %. To the resulting rubber polymer solution were added 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol as antioxidants. The analytical values of the rubber polymer P are shown in Table 2.
[0110] <(Production Example 17) Rubber-like Polymer Q> A rubber-like polymer Q was obtained in the same manner as in Production Example 15, except that the amount of 2,2-di(2-tetrahydrofuryl)propane added was changed to 2.7 g, the amount of n-butyllithium added was changed to 2.6 g, the amount of the first functionalizing agent 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) added was changed to 9.9 g, and the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of rubbery polymer Q are shown in Table 2.
[0111] <(Production Example 18) Rubber-like Polymer R> A rubber-like polymer R was obtained in the same manner as in Production Example 1, except that the amount of 2,2-di(2-tetrahydrofuryl)propane added was changed to 1.1 g, the amount of n-butyllithium added was changed to 1.0 g, the amount of the first functionalizing agent 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table) added was changed to 1.9 g, and the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubbery polymer R are shown in Table 2.
[0112] <(Production Example 19) Rubber Polymer S> A rubber-like polymer S was obtained in the same manner as in Production Example 1 above, except that the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubber polymer S are shown in Table 2.
[0113] <(Production Example 20) Rubber Polymer T> A rubber-like polymer T was obtained in the same manner as in <Production Example 2> above, except that the hydrogenation rate was adjusted by changing the amount of hydrogenation. The analytical values of the rubbery polymer T are shown in Table 2.
[0114] <(Production Example 21) Rubber-like Polymer U> A temperature-controllable autoclave having an internal volume of 43 L and equipped with a stirrer and a jacket was used as a reactor. 3,112 g of 1,3-butadiene, 258 g of styrene, 25,800 g of cyclohexane, and 2.4 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 2.2 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when this increase in temperature was no longer observed, 2.2 g of the first functionalizing agent, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (shown as X in the table), was added to the reactor and stirred for 5 minutes. A portion of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. Thereafter, the hydrogenation catalyst (TC-1) prepared in the above <Production Example α> was added to the rubber-like polymer solution before hydrogenation in an amount of 60 ppm (Ti standard) per 100 parts by mass of the rubber-like polymer before hydrogenation, and a hydrogenation reaction was carried out for 50 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C to obtain a rubber-like polymer. The hydrogenation rate of the resulting rubber-like polymer U was 85 mol %. To the resulting rubber polymer solution were added 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol as antioxidants. The analytical values of the rubbery polymer U are shown in Table 3.
[0115] <(Production Example 22) Rubber-like Polymer V> A 43 L internal volume autoclave equipped with an agitator and a jacket and capable of controlling temperature was used as a reactor. 3,112 g of 1,3-butadiene, 258 g of styrene, 25,800 g of cyclohexane, and 2.9 g of 2,2-di(2-tetrahydrofuryl)propane as a polar substance, all of which had previously been removed of impurities, were placed in the reactor, and the internal temperature of the reactor was maintained at 42°C. Subsequently, 2.8 g of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and when the temperature increase was no longer observed, 7.8 g of the first functionalizing agent, 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (denoted as Y in the table), was added to the reactor and stirred for 5 minutes. A part of the polymerization solution was withdrawn and dried to obtain a rubber-like polymer before hydrogenation. Thereafter, the hydrogenation catalyst (TC-1) prepared in the above <Production Example α> was added to the rubber-like polymer solution before hydrogenation in an amount of 60 ppm (Ti standard) per 100 parts by mass of the rubber-like polymer before hydrogenation, and a hydrogenation reaction was carried out for 50 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C to obtain a rubber-like polymer. The hydrogenation rate of the resulting rubber-like polymer V was 85 mol %. To the resulting rubber polymer solution were added 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol as antioxidants. The analytical values of rubbery polymer V are shown in Table 3.
[0116] <(Production Example 23) Rubber-like Polymer W> A rubber-like polymer W was obtained in the same manner as in <Production Example 3> above, except that the amount of 2,2-di(2-tetrahydrofuryl)propane added was changed to 2.0 g, the amount of n-butyllithium added was changed to 1.8 g, and the amount of the first functionalizing agent 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine (represented as X in the table) added was changed to 1.9 g. The analytical values of the rubbery polymer W are shown in Table 3.
[0117] <(Production Example 24) Rubber-like Polymer X> A rubber-like polymer X was obtained in the same manner as in <Production Example 4> above, except that the first functionalizing agent was changed to tetrachlorosilane and the amount added was changed to 4.2 g. The analytical values of the rubbery polymer X are shown in Table 3.
[0118] [Table 1]
[0119] [Table 2]
[0120] [Table 3]
[0121] [Examples 1 to 16 (Production Examples 25 to 40)], [Comparative Examples 1 to 7 (Production Examples 41 to 47)] (Preparation of Rubber Composition Solution) The solutions of the rubber polymers produced as described above were mixed in the following manner to obtain solutions of the rubber compositions (a to w). How to mix the rubbery polymer solution: According to the blend ratios in Tables 4 to 6, two types of rubber polymer solutions were added to a 10 L stirring tank equipped with an agitator. After the addition, the mixture was mixed by continuing stirring for 2 minutes under the following stirring conditions. <Stirring conditions> Temperature: 60℃ Liquid volume: 10L Mixing tank: 10L mixing tank with impeller Agitator blades: 2 turbine blades Agitator rotation speed: 200 rpm
[0122] (Production of rubber composition molded article) The solvent was removed from the rubber composition solution prepared as described above by a steam stripping method described below to obtain crumbs of a rubber composition molded body. The crumbs were then dried and compressed by the method described below to obtain a rubber composition molded body. The conditions for the steam stripping process are as follows: <Conditions for the steam stripping method> Water temperature: 90℃ Water amount: 15kg Mixing tank: 50L mixing tank with impeller Agitator blades: 2 turbine blades Agitator rotation speed: 500 rpm Amount of polymer used for steam stripping: 500g Addition rate of solution to the stirring tank: 30g / min
[0123] The method for compressing the crumb is as follows: <How to compress crumbs> 35 kg of the crumbs prepared by the above method were heated to 60°C and filled into a rectangular container with dimensions of 42 cm long, 21 cm short, and 40 cm deep, and compressed with a cylinder at a pressure of 3.5 MPa for 10 seconds to obtain a rubber composition molded product.
[0124] (Analysis of rubber composition and rubber composition molded article) The physical properties of the obtained rubber compositions and rubber composition molded articles, as well as the results of the following <Evaluation 1>, are shown in Tables 4 to 6.
[0125] <Evaluation 1: Evaluation of composition unevenness in rubber composition molded body> In order to evaluate the composition unevenness resulting from the uneven mixing in the rubber composition molded article obtained as described above, three samples were taken from any positions of the rubber composition molded article, and the Mooney viscosity at 100° C. was measured for each sample. The compositional unevenness in the rubber composition molded article was evaluated by calculating a standard deviation from the difference between the 100° C. Mooney viscosity values at the three points. The lower the standard deviation value, the more uniform the composition is in the rubber composition molded product, and the more uniform the mixing of the rubber polymers is.
[0126] [Table 4]
[0127] [Table 5]
[0128] [Table 6]
[0129] It was found that, compared with Comparative Examples 1-7, Examples 1-16 had smaller compositional unevenness in the rubber composition molded article.
[0130] [Examples 17 to 32 (Production Examples 48 to 63)], [Comparative Examples 8 to 14 (Production Examples 64 to 70)] (Preparation of rubber composition for crosslinking, evaluation of physical properties) Using the rubber compositions a to w obtained in Production Examples 25 to 47 shown in Tables 4 to 6 as raw rubbers, rubber compositions for crosslinking containing each raw rubber were obtained according to the formulation shown below. The compounding conditions are shown below.
[0131] (Combination conditions) The amount of each compounding ingredient added is shown in parts by mass per 100 parts by mass of the rubber component not including the rubber softener. Rubber compositions a to w: 100.0 parts by mass Silica 1 (product name "Ultrasil 7000GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m2 / g): 50.0 parts by mass Silica 2 (Rhodia's product name "Zeosil Premium 200MP" nitrogen adsorption specific surface area 220 m2 / g): 25.0 parts by weight Carbon black (product name "Seat KH (N339)" manufactured by Tokai Carbon Co., Ltd.): 5.0 parts by weight Silane coupling agent (product name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass SRAE oil (product name "Process NC140" manufactured by JX Nippon Oil & Energy Corporation): 25.0 parts by mass ·Zinc white: 2.5 parts by mass Stearic acid: 1.0 parts by weight Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass ·Sulfur: 2.2 parts by mass Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazylsulfinamide): 1.7 parts by mass Vulcanization accelerator 2 (diphenyl guanidine): 2.0 parts by mass ·Total: 222.4 parts by mass
[0132] (Mixing method and evaluation of moldability of rubber composition) The above materials were kneaded by the following method to obtain a crosslinkable rubber composition. Using an internal mixer (capacity: 0.3 L) equipped with a temperature control device, the raw rubber, fillers (silica 1, silica 2, carbon black), silane coupling agent, SRAE oil, zinc oxide, and stearic acid were mixed in the first stage at a filling rate of 65% and a rotor rotation speed of 30 to 50 rpm. At this time, the temperature of the internal mixer was controlled so that the discharge temperature was 155 to 160° C., and each rubber composition (compound) was obtained. Next, in the second stage of kneading, the mixture obtained above was cooled to room temperature, and then the antioxidant was added and kneaded again to improve the dispersion of the silica. In this case, the discharge temperature of the mixture was adjusted to 155 to 160°C by controlling the temperature of the mixer. After cooling, in the third stage of kneading, sulfur and vulcanization accelerators 1 and 2 were added and kneaded with an open roll set at 70° C. After kneading, the moldability of the rubber composition was evaluated based on the surface roughness of the sheet of the rubber composition for crosslinking discharged from the open roll. Thereafter, the rubber composition was molded and vulcanized at 160° C. for 20 minutes in a vulcanizing press, and the vulcanized rubber composition was evaluated. Specifically, the evaluation was performed by the following methods. The results are shown in Tables 7 to 9.
[0133] <Evaluation 2: Moldability of rubber composition> The moldability of the rubber composition was evaluated by visual observation according to the following indices. 5: The surface of the sheet discharged from the roll is sufficiently clean, and the edges of the sheet are not cracked. 4: The surface of the sheet coming off the roll is clean, and there are no noticeable cracks on the edges of the sheet. 3: There are no noticeable irregularities on the surface of the sheet discharged from the roll, but cracks are observed on the edges of the sheet. 2: The surface of the sheet coming off the roll is uneven, and most of the edge of the sheet is cracked. 1: The rubber composition discharged from the roll is not in a sheet form.
[0134] <Evaluation 3: Tensile strength> The tensile strength was measured in accordance with the tensile test method of JIS K6251. In Tables 7 to 9, the evaluation results of Examples 17 to 32 and Comparative Examples 8 to 14 are indexed, with the tensile strength of Example 22 (Production Example 53) set at 100. A larger index indicates better tensile strength.
[0135] <Evaluation 4: Abrasion resistance> Abrasion resistance was measured in accordance with the DIN abrasion test of JIS K6264-2. In Tables 7 to 9, the evaluation results of Examples 17 to 32 and Comparative Examples 8 to 14 are indexed based on the abrasion resistance of Example 22 (Production Example 53) being 100. The larger the index, the more excellent the abrasion resistance.
[0136] [Table 7]
[0137] [Table 8]
[0138] [Table 9]
[0139] As shown in Tables 7 to 9, it was confirmed that Examples 17 to 32 were superior to Comparative Examples 8 to 14 in terms of the balance of moldability, tensile strength, and abrasion resistance of the rubber composition. [Industrial Applicability]
[0140] The rubber composition of the present invention is suitable as a constituent material of a rubber composition for crosslinking, and specifically has industrial applicability in the fields of tire components, interior and exterior parts of automobiles, anti-vibration rubber, belts, footwear, foams, various industrial product applications, and the like.
Claims
1. The iodine value is 10 to 270 g / 100 g, Contains 3% by mass or more of an ethylene structure, The amount of vinyl aromatic monomer blocks is 10% by mass or less, The content of vinyl aromatic monomer units is 5% by mass or more, In the molecular weight distribution of the rubber-like polymer determined by gel permeation chromatography (GPC), there is at least one peak at a molecular weight of 350,000 or more; and has at least one peak at a molecular weight of 5,000 to less than 350,000; In a gel permeation chromatography (GPC) measurement using a viscometer, the average branching degree of a rubber-like polymer having a molecular weight of 350,000 or more is 3 or more; A rubber composition in which, in a GPC molecular weight distribution curve, the area of a rubber-like polymer having a molecular weight of 350,000 or more is defined as AA, and the area of a rubber-like polymer having a molecular weight of 5,000 to less than 350,000 is defined as BA, and the ratio of BA to the total area of AA and BA (BA) / (AA+BA) is 50% or more and 90% or less.
2. In the GPC molecular weight distribution curve, The highest molecular weight peak top molecular weight Mp is 650,000 or more. The rubber composition according to claim 1.
3. The content of α-olefins other than vinyl aromatic monomer units is 15% by mass or more. The rubber composition according to claim 1 or 2.
4. The rubber composition according to claim 1 , further comprising a nitrogen atom.
5. The modification rate measured by column adsorption GPC method is 20% by mass or more. The rubber composition according to any one of claims 1 to 4.
6. The modification rate measured by column adsorption GPC method is The modification rate of the rubber-like polymer having a molecular weight of 350,000 or more is 60 mass% or more. The rubber composition according to any one of claims 1 to 5.
7. The silicon content is 50 ppm or more. The rubber composition according to any one of claims 1 to 6.
8. The branching degree of the rubber-like polymer in the molecular weight region of 350,000 or more is greater than the branching degree of the rubber-like polymer in the molecular weight region of less than 350,000. The rubber composition according to any one of claims 1 to 7.
9. The Mooney Relaxation Ratio (MSR) is 0.5 or less. The rubber composition according to any one of claims 1 to 8.
10. The rubber composition according to any one of claims 1 to 9, A cross-linking agent; Contains The crosslinking agent is contained in an amount of 0.1 parts by mass or more and 20 parts by mass or less based on 100 parts by mass of the rubber component. Crosslinkable rubber composition.
11. A method for producing a rubber composition molded article using the rubber composition according to any one of claims 1 to 9 or the rubber composition for crosslinking according to claim 10, comprising the steps of: A step of polymerizing a rubber-like polymer A having a peak top of a molecular weight of 350,000 or more; a step of polymerizing a rubber-like polymer B having a peak top in a molecular weight range of 5,000 to less than 350,000; A step of mixing the rubber polymer A and the rubber polymer B in a solution to obtain a mixed solution; removing the solvent from the mixed solution to obtain a rubber composition; A step of molding using the rubber composition; having, A method for producing a rubber composition molded article.
12. A method for producing a rubber composition molded article using the rubber composition according to any one of claims 1 to 9 or the rubber composition for crosslinking according to claim 10, comprising the steps of: A step of polymerizing a rubber-like polymer A having a peak top of a molecular weight of 350,000 or more; a step of polymerizing a rubber-like polymer B having a peak top in a molecular weight range of 5,000 to less than 350,000; adding two or more types of functionalizing agents having different branching degrees to the rubber polymer A and the rubber polymer B, respectively, to functionalize the polymer chain ends; removing the solvent from the polymerization solution to obtain a rubber composition; The method includes a step of molding the obtained rubber composition. A method for producing a rubber composition molded article.
13. A tread for a tire, comprising the rubber composition according to any one of claims 1 to 9 or the rubber composition for crosslinking according to claim 10.
Citation Information
Patent Citations
Rubber composition
JP1985252643A
Hydrogenated diene based polymer rubber composition
JP1988041547A
Rubber composition
JP1990147646A
Rubber composition
JP1995233285A
Rubber composition for improved tire tread
JP1996120119A